Design of Hybrid Portable Underwater Turbine Hydro and Solar Energy Power Plants: Innovation to Use Underwater and Solar Current as Alternative Electricity in Dusun Dongol Sidoarjo - Anggara Trisna Nugraha; Dadang Priyambodo (Department of Electromedical Engineering, POLTEKKES KEMENKES SURABAYA and IKATEMI, 2021)
The need for electrical energy in Indonesia continues to increase every year. In line with the increase in the electrification ratio to 100% in 2050, the demand for electrical energy is projected to reach 7 times, namely 1,611 TWh. To meet electricity needs, the government has created a 35 GW program, but one of the largest contributors to power generation fuel is coal with a share of 58% or around 50 GW which is estimated to be exhausted within the next 68 years. For this reason, innovations are needed in terms of fulfilling electrical energy by utilizing renewable energy potential, one of which is hydro energy, which is 45,379 MW from a total resource of 75,091 MW. Therefore, from this potential, innovations related to renewable energy have been created, namely the Hybrid Portable Underwater Turbine Hydro and Solar Energy hybrid power plant. This power plant uses an undersea current as a propulsion which is hybridized with solar power to increase the production of electrical energy. This power plant has the advantage that there is an Underwater turbine design that is resistant to underwater flow and a water flow direction to increase the work efficiency of the underwater turbine. From the test results, the portable Underwater turbine hydro produces 950 W in a day. Solar panels produce 65.6 Watts a day. The total hybrid that can be produced is 1.02 kW a day. In its implementation it can supply loads of up to 900 (VA) such as lamps, fans, TV, etc. This hybrid power plant can be a solution to help meet electricity needs in the area around Dusun Dongol, Sidoarjo through alternative electrical energy innovations.